A Validated Stability-Indicating RP-HPLC Method for Quantification of Glycyrrhizic Acid and Piperine in Polyherbal Formulations: Quantification of Glycyrrhizic Acid and Piperine: A Stability-Indicating RP-HPLC Method - Koli, Rahul; Mannur, Vinodhkumar. S.; Gharge, Shankar; Gudasi, Sachin (Iranian Journal of Pharmaceutical Sciences, 2024)
Glycyrrhizic acid and piperine are frequently used in conjunction with other therapies to treat a variety of disorders, although both medications have low water solubility and photosensitivity issues. The objective of this study is to develop a Reverse-phase High-Performance Liquid Chromatography (RP-HPLC) method, known for its selectivity, precision, sensitivity, and accuracy. This method is intended for the quantification of phytoconstituents in formulating polyherbal tablets as well as in certain Ayurvedic formulations. Glycyrrhizic acid and piperine were successfully separated by liquid chromatography using the phenomenex Luna C-18 column and an isocratic elution mode with a mobile phase made up of a combination of methanol and HPLC grade water. A photodiode array (PDA) detector was used to determine the retention times for glycyrrhizic acid and piperine, which were determined to be 2.06 minutes and 9.0 minutes and the method was found to be accurate (>95%) and precise (%RSD < 25) respectively. The method was established to be specific for the quantification of glycyrrhizic acid and piperine in in-house polyherbal tablets and some Ayurvedic formulations. Additionally, both phytoconstituents stress degradation studies were examined, and in the presence of degradation products, good drug peak separation was observed. Thus, glycyrrhizic acid and piperine may be regularly estimated in vitro and in vivo using this method.